Pendidikan Manajemen Perawatan Diri Diabetes dalam Meningkatkan Aktivitas Perawatan Diri Pasien Diabetes: Studi Kuasi-Eksperimental - Noor Diani; Elly Nurachmah; Debie Dahlia; Evi Martha; M. Fakhruddin Noor; Rizka Hayyu Nafi’ah (PT.Mantaya Idea Batara, 2026)
Background: Diabetes mellitus is a chronic condition requiring continuous self-management. Appropriate self-care practices are essential for glycemic control and prevention of complications; however, local evidence on educational interventions remains limited. This study aimed to determine the effect of diabetes self-care management education on self-care activities among patients with type 2 diabetes mellitus. Methods: A quasi-experimental, one-group pretest–posttest design was used. Forty patients with type 2 diabetes mellitus who met the inclusion criteria were recruited. Self-care activities were assessed using the Summary of Diabetes Self-Care Activities (SDSCA) before and after the educational intervention. Result: The mean SDSCA score increased from 4.89 to 6.12 after the intervention, showing a statistically significant improvement (p < 0.001). Conclusion: Diabetes self-care management education improved self-care activities among patients with type 2 diabetes mellitus. Clinically, this intervention may support routine diabetes care by strengthening patient engagement in daily disease management. Nevertheless, the one-group design limits causal interpretation because no control group was used. Future studies with controlled design and larger samples are recommended.